1981
DOI: 10.1002/bip.1981.360200410
|View full text |Cite
|
Sign up to set email alerts
|

Binding of ligands to a one‐dimensional heterogeneous lattice. II. Intercalation of tilorone with DNA and polynucleotides

Abstract: SynopsisThe interaction of tilorone with DNA and five synthetic polydeoxyribonucleotides [(I): poly[d(G-C)]; (IV): poly(dG).poly(dC); and (V): poly(dA)-poly(dT)] has been investigated. Binding isotherms for the homopolymers were obtained by microdialysis equilibria using ''CC-labeled tilorone and interpreted with different models: exclusion effect, associated or not associated with cooperativity, or variable exclusion. Affinity appears to be related more to local structure than to base composition and decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Long-range structural distortions of DNA remote from the site of intercalation are also frequently observed (Neidle and Abraham, 1984;Neidle et al, 1987). Tilorone almost certainly produces such effects since it was found to remove and reverse the supercoiling of PM2 DNA and to decrease the sedimentation coefficient of nicked circular PM2 DNA in the fashion characteristic of intercalating agents (Wright et al, 1980).Although the apparent association constant for tilorone binding to calf thymus DNA is similar to that of ethidium (Chandraand Woltersdorf, 1976) the helix unwinding angle for tilorone is much lower than that of ethidium (Wright et al, 1980;Sturm et al, 1981). Clearly explanation (1) for the enhancement of DNAase I cutting must be carefully considered.…”
Section: Sequence-selective Binding Of Tilorone To Dna and Comparisonmentioning
confidence: 90%
See 1 more Smart Citation
“…Long-range structural distortions of DNA remote from the site of intercalation are also frequently observed (Neidle and Abraham, 1984;Neidle et al, 1987). Tilorone almost certainly produces such effects since it was found to remove and reverse the supercoiling of PM2 DNA and to decrease the sedimentation coefficient of nicked circular PM2 DNA in the fashion characteristic of intercalating agents (Wright et al, 1980).Although the apparent association constant for tilorone binding to calf thymus DNA is similar to that of ethidium (Chandraand Woltersdorf, 1976) the helix unwinding angle for tilorone is much lower than that of ethidium (Wright et al, 1980;Sturm et al, 1981). Clearly explanation (1) for the enhancement of DNAase I cutting must be carefully considered.…”
Section: Sequence-selective Binding Of Tilorone To Dna and Comparisonmentioning
confidence: 90%
“…Theoretical (Chen et sl., 1988) and experimental (Chandra et al, 1972b;Chandra and Woltersdorf, 1976) studies have both suggested that tilorone binds predominantly to AT-rich DNA sequences. Further investigations of the binding of tilorone to various synthetic polynucleotides have revealed a preference for alternating pyrimidine-purine sequences, not restricted to the poly(dA-d1) polymer (Sturm et al, 1981;Sturm, 1982). But caution must be exercised in using synthetic polynucleotides as models for base sequence specificity.…”
Section: Introductionmentioning
confidence: 98%
“…2 Again, in the computer program, minor modifications and additions in the tests of step 2 of the basic model are sufficient to solve the problem.…”
Section: Model With Varying Exclusion Numbermentioning
confidence: 99%
“…refers to the concentrations of free dye calculated from the binding isotherms reported previous1y.l The concentration of available binding sites, s, is calculated from the extent of binding r , the concentration of nucleotides P , and the exclusion number n'. 12 The concentration dependence of the relaxation times were obtained by using a series of solutions having different DNA concentrations but the same degree of binding r . This was done by diluting a concentrated stock solution of the complex with various amounts of a tilorone solution at a concentration B.…”
Section: For Poly[d(a-t)]-poly[d(a-t)] Poly[d(a-c)]poly[d(g-t)] Pomentioning
confidence: 99%